CAUSAL FACTORS AND SOLUTIONS TO LEARNING DIFFICULTIES IN ARABIC IN CLASS XI IPS MADRASAH ALIYAH MUHAMMADIYAH 1 MEDAN-NORTH SUMATERA - Siti Rahma; Azizah Sabrina Gajah; Ernida Hasibuan; Sahkholid Nasution (Jurnal Eduslamic, 2025)
This research is motivated by the problem of students who have difficulty in learning Arabic. So the researcher raised the title related to "Causal Factors and Solutions to Arabic Learning Difficulties in Class XI IPS MAS Muhammadiyah 1 Medan". The purpose of this research is to find out the factors that cause students to have difficulty in learning Arabic and solutions or strategies in overcoming learning difficulties in Arabic. This research applies descriptive qualitative research methods with collection methods namely interviews, observation and documentation. The results of the research obtained are found various factors, namely internal factors and external factors that cause students to feel difficulties in learning Arabic. Internal factors are divided into 2, namely first, physiological factors such as illness or disability. Second, psychological factors such as intelligence, talent, interest, motivation, mental health factors and special kinds of learners. While external factors include the family environment, school environment and community environment. The solution to overcome students' difficulties in learning Arabic at Madrasah Aliyah Muhammadiyah 1 Medan is by using several learning media that are considered effective such as using audio-visual-based learning media, namely using learning videos or watching Arabic cartoons, applying ice breaking before starting learning, and playing games.